Implementation of the teleconsultation service with an emphasis on gastroenterology in the San Pablo Clinic Network (Peru) during the COVID-19 pandemic - Huapaya-Huertas, Oscar (2023)
Objective: To describe the assistance provided by the teleconsultation service in the San Pablo Clinic Network (RCSP) during the COVID-19 pandemic, with an emphasis on the specialty of gastroenterology. The study: Descriptive study. Data from the Electronic Medical Records System and the RCSP administrative system were reviewed. Results: The RCSP includes 8 locations (5 in Lima). Between April 2020 and December 2021, 1,156,253 visits were made (6.6% of these by teleconsultation). The specialties with the most teleconsultations were internal medicine and endocrinology, and the specialties with the most face-to-face consultations were gynecology-obstetrics and traumatology. Gastroenterology was the ninth most frequent specialty in teleconsultation and the fifth in face-to-face consultation. The most frequent diagnoses of this specialty, both for face-to-face consultation and teleconsultation, were dyspepsia and gastroesophageal reflux disease Conclusion: The implementation of the teleconsultation service in the RCSP is reported. In addition, lessons learned in this process are provided.